Secretome Conveys the Protective Effects of ASCs: Therapeutic Potential Following Hemorrhagic Shock?. Issue 4 (October 2018) - Ashmwe, Mostafa; Penzenstadler, Carina; Bahrami, Arian; Klotz, Anton; Jafarmadar, Mohammad; Banerjee, Asmita; Wolbank, Susanne; Redl, Heinz; Bahrami, Soheyl
ABSTRACT: Objectives: We tested whether resuscitation supplemented with rat adipose-derived stem cells (ASCs) or secretome (conditioned media) of ASCs can ameliorate inflammation, cell/organ injury, and/or improve outcome after hemorrhagic traumatic shock (HTS). Interventions: Rats were subjected to HTS and a resuscitation protocol that mimics prehospital restrictive reperfusion followed by an adequate reperfusion phase. Twenty minutes into the restrictive reperfusion, animals received an intravenous bolus of 2 × 10 6 cells (ASC group) or the secretome produced by 2 × 10 6 ASCs/24 h (ASC-Secretome group). Controls received the vehicle (Vehicle group). All rats were observed for 28-day survival. Measurements and Main Results: HTS-induced inflammation represented by IL-6 was inhibited in the ASC (80%, P < 0.001) and in ASC-Secretome (59%, P < 0.01) group at 48 h compared with Vehicle group. At 24 h, HTS-induced liver injury reflected in plasma alanine aminotransferase was ameliorated by 36% ( P < 0.001) in both the ASC and ASC-Secretome groups when compared with the Vehicle. There was no effect on kidney function and/or general cell injury markers. HTS induced a moderate 28-day mortality (18%) that was prevented ( P = 0.08) in the ASC but not in the ASC-Secretome group (12%). Conclusions: Our data suggest that the ASC-secretome supplemented resuscitation following HTS, in the absence of the stem cells, exerts anti-inflammatory and liver protective effects. Given its ease of preparation, storage, availability, and application (in contrast to the stem cells) we believe that the cell-free secretome has a better therapeutic potential in the early phase of an acute hemorrhagic shock scenario. Abstract : Supplemental Digital Content is available in the text